On Adding a Dental Practice Component to an Ongoing Longitudinal Population-based Study of Oral Health - Gregg H. Gilbert, DDS, MBA; John S. Rose, MPH; Elmire D. Cantey, BS, RDH; Janet L. Earls, BS, RDH; (Blackwell Synergy, 2002)
To determine the feasibility and effectiveness of adding a dental practice component to the Florida Dental Care Study (FDCS